Odyniec po drugiej stronie lustra - Szargot, Maciej (Tematy i Konteksty, 2016)
The article is a review of the book by Maria Makaruk, Antoni Edward Odyniec – romantyk w zwierciadle biedermeieru, which was published in Warsaw in 2012. The book is devoted to the life and works of the poet connected with two literary currents, Romanticism and Biedermeier. This interesting and valuable volume is complemented by an anthology of Odyniec’s works.